2005
DOI: 10.1080/13556210500123191
|View full text |Cite
|
Sign up to set email alerts
|

Mood and affect during detoxification of opiate addicts: a comparison of buprenorphine versus methadone

Abstract: Twenty-six in-patients with Diagnostic and Statistical Manual version IV (DSM-IV) criteria for opioid dependence were selected at random to receive either a combination of an 11-day low-dose buprenorphine and a 14-day carbamazepine regimen (n = 14) or a combination of an 11-day methadone and a 14-day carbamazepine regimen (n = 12) in a double-blind, randomized 14-day in-patient detoxification treatment. Patients with buprenorphine and carbamazepine showed a significantly better psychological state after the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 57 publications
1
11
0
1
Order By: Relevance
“…The lack of significant group differences in depressive symptoms, which are more strongly associated with methadone maintenance treatment (Seifert et al, 2005), may be 1 explanation for this inconsistency. Future studies should examine in more detail under which conditions different pharmacological treatments are more beneficial for adaptive decision making.…”
Section: Substance Use Parameters/pharmacological Variables--lifetimementioning
confidence: 67%
See 1 more Smart Citation
“…The lack of significant group differences in depressive symptoms, which are more strongly associated with methadone maintenance treatment (Seifert et al, 2005), may be 1 explanation for this inconsistency. Future studies should examine in more detail under which conditions different pharmacological treatments are more beneficial for adaptive decision making.…”
Section: Substance Use Parameters/pharmacological Variables--lifetimementioning
confidence: 67%
“…On the basis of the observation that opioid-dependent patients substituted with buprenorphine showed better decision-making performances than those receiving methadone, Pirastu et al (2006) also argued for distinct pharmacological effects on decision-making processes associated with the different opioid-replacement therapies. Considered in more detail, these differential treatment effects may be due to the more-severe sedative and depressive symptoms associated with methadone as compared with buprenorphine and the side effects' adverse influences on decision-making performance (Seifert et al, 2005;Must et al, 2006).…”
mentioning
confidence: 99%
“…It is noteworthy, that when Doehring et al [43] analyzed the whole DRD2 gene locus they found that DRD2 genetic polymorphisms regulate both opiate addiction risk and ORT dosage requirements. Relevant to this article Seifert et al [27] found that compared to carbamazepine and methadone, patients on the buprenorphine and carbamazepine combination demonstrated significantly better psychological state with reduced, sensitiveness, tiredness and depression by week two of detoxification. Once again this work adequately supports the short term use of buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…3A4 inducers such as carbamazepine and barbiturates result in clinically significant lowering of methadone drug levels, resulting in the emergence of withdrawal symptoms and raising of methadone doses for symptom stabilization. Notably, Seifert [27] found better clinical outcomes and more effective short-term relief of affective disturbances resulted from combining buprenorphine and carbamazepine than from combining carbamazepine with methadone when detoxifying multi-drug opiate addicts. An explanation of this interesting effect may be that while buprenorphine has similar effects on enzyme induction as methadone the reported difference could be due to buprenorphine’s high affinity and slow dissociation receptor binding characteristics.…”
Section: Pharmacokinetics Of Mixed Agonist/antagonists Of Opiate Recementioning
confidence: 99%
“…In contrast to this study, there is no evidence from our data for fewer withdrawal symptoms or a shorter duration of detoxification with buprenorphine. In a further study, Seifert et al 44 reported that opioid-dependent inpatients on buprenorphine/carbamazepine during withdrawal treatment demonstrated less daytime fatigue and depressive states than did patients treated with methadone/ carbamazepine. This finding is very much in accordance with reduced daytime activity found here as actigraphic correlate in the methadone group.…”
Section: Discussionmentioning
confidence: 96%